The Effect of Electronic Tax System on the Financial Performance of Small and Medium Businesses in Burundi Case Study of Rohero District - Danie Stella Igiraneza (Uganda Christian University, 2024)
The purpose of the study was to examine the effect of electronic tax system has on the financial performance of small and medium sized entreprises.in Rohero district. The study was based on three objectives: to determine the effect of tax registration on the financial performance of the small and medium enterprises; to assess the effect the effect of electronic tax payment on the financial performance of small and medium enterprises and to determine the effect of electronic tax determination on the financial performance of small and medium enterprises. It was based on a descriptive survey design on the use of qualitative and quantitative approaches that was adopted to examine the effects of electronic tax system on the financial performance of small and medium businesses. Questionnaires and interview were used to collect primary and secondary sources of data from 30 respondents using a random sampling. Data analysis was done using SPSS. It is made out of five chapters where they consecutively give an overview of the study including the objectives and problem statement; the literature review; the data collection methods; the data analysis and interpretation and the summary conclusions recommendations. The study was carried out over a four months’ period from April to August 2024.
Undergraduate research